Diversity and Colonization Strategies of Endolithic Cyanobacteria in the Cold Mountain Desert of Pamir - Nataliia Khomutovska; Asunción de los Ríos; Iwona Jasser (Microorganisms, 2020)
Microorganisms can survive in extreme environments and oligotrophic habitats thanks to their specific adaptive capacity. Due to its severe and contrasting climate conditions, the cold mountain desert in Eastern Pamir provides a unique environment for analyzing microbial adaptation mechanisms occurring within colonization of endolithic habitats. This study aims to investigate the composition and structure of endolithic microbial communities and analyze the interactions between microorganisms and colonized lithic substrates. Endolithic biofilms were examined using scanning electron microscopy in backscattered electron mode (SEM-BSE) and next-generation sequencing (NGS) applying amplicon sequence variants (ASVs) approach. The investigation of the V3–V4 region of 16S rRNA gene revealed that endolithic communities are dominated by Actinobacteria (26%), Proteobacteria (23%), and Cyanobacteria (11.4%). Cyanobacteria were represented by Oxyphotobacteria with a predominance of subclasses of Oscillatoriophycidae, Synechococcophycideae, and Nostocophycidae as well as the rarely occurring Sericytochromatia. The positive correlation between the contribution of the orders Synechococcales and Rhizobiales to community structure suggests that some functionally closed taxa of Cyanobacteria and Proteobacteria can complement each other, for example, in nitrogen fixation in endolithic communities. The endolithic communities occurring in Eastern Pamir were identified as complex systems whose composition and structure seem to be influenced by the architecture of microhabitats and related microenvironmental conditions.